Epigenetic control of antigen presentation failure in osteosarcoma: from single-cell chromatin maps to therapeutic strategies - He, Yan; Wu, Heng (Frontiers in Immunology, 2025)
Osteosarcoma arises within heterogeneous tumor–immune ecosystems in which impaired antigen visibility—shaped by chromatin programs—limits immune surveillance and blunts responses to immunotherapy. Beyond structural defects in the antigen-processing pathway, Polycomb-mediated repression, DNA hypermethylation, and state-specific enhancer closure converge on the HLA class I/NLRC5/interferon axis to diminish peptide display. These constraints are context dependent, varying across malignant clones, differentiation states, and myeloid and T-cell niches. Traditional bulk assays obscure this complexity; single-cell ATAC-seq, integrated with single-cell and spatial transcriptomics, now resolves promoter–enhancer accessibility at HLA, NLRC5, and antigen-processing genes, distinguishes reversible repression from fixed lesions, and links microenvironmental stress to interferon competence. Translationally, epigenetic reprogramming—targeting Polycomb repressive complex 2 (PRC2), DNA methyltransferases (DNMTs), and complementary regulators (for example, LSD1, BET, CDK4/6, YAP/TEAD)—offers biomarker-guided avenues to restore antigen presentation, provided ecosystem-aware pharmacodynamic readouts track chromatin opening and antigen-presentation recovery across compartments. Despite encouraging preclinical evidence, efficacy will depend on clone selection, scheduling that preserves interferon signaling, and rational combinations with innate agonists and checkpoint blockade. This mini-review synthesizes epigenetic mechanisms of antigen-presentation failure in osteosarcoma and outlines how single-cell chromatin profiling can guide strategies to reinstate tumor antigen visibility.